Historical Development of Human Cognition A Cultural-Historical Neuropsychological Perspective - Ardila, Alfredo (Perspectives in Cultural-Historical Research, 2018)
This book addresses a central question: how did cognition emerge in human history? It approaches the question from a cultural-historical, neuropsychological perspective and analyses evidence on the historical origins of cognitive activity; integrates information regarding cross-cultural differences in neuropsychological performance; and discusses how adopting a historical and cultural perspective in the behavioural neurosciences can help to arrive at a better understanding of cognition. Lastly, it proposes general guidelines for future research in the area.